Enterprise resource planning and supply chain management : functions, business processes and software for manufacturing companies - Kurbel, Karl, 1947- (Springer, 2013)
"This book is about running modern industrial enterprises with the help of information systems. Enterprise resource planning (ERP) is the core of business information processing. An ERP system is the backbone of most companies' information systems landscape. All major business processes are handled with the help of this system. Supply chain management (SCM) looks beyond the individual company, taking into account that enterprises are increasingly concentrating on their core competencies, leaving other activities to suppliers. With the growing dependency on the partners, effective supply chains."
"Progress in IS"--Z obálky
Keywords: podnikové informační systémy; informační management; logistika (management); management information systems; information management; business logistics; monografie; monographs